Safety of Rivaroxaban For Prophylaxis Vein Thrombosis Post Total Hip and Knee Replacement - Luthfiyanti, Niken; Jayak Pratama, Kharisma; Noviana, Noviana (LPPM Universitas Duta Bangsa Surakarta, 2024)
Orthopaedic surgery such as surgery on the pelvis and knee bones has a high risk of developing Deep Vein Thromoembolism (DVT), especially in patients with hypercoagulability. Venous thromboembolism is the main cause of morbidity and mortality in orthopedic patients that can be prevented using thromboprophylaxis, but on the other hand is related to the risk of bleeding side effects. The study aimed to evaluate the safety of oral Rivaroxaban prophylaxis in patients after Total Hip and Knee Replacement. This research applied cross sectional technique. Retrospective data were taken from the medical records of Dr. Moewardi Surakarta, period January 2023- July 2024. The data taken are secondary data from the patient's medical record by recording clinical symptoms that appear. Rivaroxaban safety evaluation includes the incidence rate of bleeding as well as the factors that influence the occurrence of bleeding. A total of 38 patients met the inclusion criteria of the study. Bleeding occurred in 4 cases (10.5%). Factors that affect the incidence of bleeding renal failure (p = 0.001). Monitoring of Rivaroxaban side effects is indispensable. Pharmaceuticals can play an important role in monitoring and preventing the occurrence of bleeding by paying attention to risk factors, especially kidney failure.